Epidemiological Study of Stroke Disease in the Southeast Maluku Islands Region in 2023 - Paliyama, Febryn Prisiliya; Rinaldi, Fransiskus Xaverius; Silalahi, Parningotan Yosi; Nari, Janti Pare (Universitas Airlangga, 2025)
Highlight: The prevalence of stroke in Southeast Maluku is 14.1 per 1,000 population for 2023. Ischemic stroke is the most common type of stroke in the Southeast Maluku Islands. The most prevalent chronic disease among stroke patients in Southeast Maluku Islands is hypertension. ABSTRACT Introduction: Stroke is a serious health problem with a high mortality rate and incidence, especially in low- and middle-income regions like Southeast Maluku, Indonesia. Inadequate facilities and risk factors causing high stroke rates in this region provide major healthcare challenges. Epidemiological data highlight the pressing need for healthcare development. Objective: This epidemiological study aimed to provide insight on the prevalence of stroke in the Southeast Maluku Islands in 2023, with the goal of enhancing the urgency of measures to reduce stroke incidences there. Methods: This study used a descriptive methodology with a cross-sectional design. Data were collected by obtaining thorough medical records from stroke patients at Karel Sadsuitubun Regional General Hospital. Demographic information, stroke type, and comorbidities were analyzed, as well as the prevalence rate calculated from the entire patient population of 8,436 as reported in 2023, while also classifying patients by age and gender. Results: In the Southeast Maluku Islands, 107 stroke cases were reported, equal to a stroke prevalence rate of 12.6 per 1,000 people. The most common type was ischemic stroke (95.33%), followed by hemorrhagic stroke (4.67%). Hypertension, which affected 67.2% of patients, was the most common comorbidity, followed by type II diabetes mellitus and coronary artery disease. Conclusion:Stroke rates have increased in the Southeast Maluku Islands due to a variety of factors, including socioeconomic conditions and unhealthy lifestyles. The study’s findings emphasize the urgent need for interventions to reduce stroke rates.